Mesenchymal stem cell-derived extracellular vesicles: current advances in preparation and therapeutic applications for neurological disorders - Li, Shuang; Zhang, Jiayi; Sun, Luyao; Yang, Ze; Liu, Xinxing; Liu, Jianling; Liu, Xifu (Frontiers in Cell and Developmental Biology, 2025)
Extracellular vesicles (EVs), nanoscale vesicles released by various cell types, have garnered significant attention in regenerative medicine. Mesenchymal stem cell-derived EVs (MSC-EVs) exhibit unique advantages, including their compact size, ability to traverse the blood-brain barrier (BBB), low immunogenicity, and high biosafety profile. However, challenges such as standardization of isolation protocols, establishment of quality control criteria, and scalability of production remain unresolved. This review critically examines the methodologies for preparation, characterization, and pharmacokinetic profiling of MSC-EVs, alongside their therapeutic potential in neurological disorders. By synthesizing current advancements, this work aims to elucidate the translational value of EVs in clinical practice. Additionally, it seeks to accelerate their transition from preclinical research to therapeutic applications, and provide a robust theoretical foundation for novel strategies in treating neurological diseases.